Obesity or undernourishment? Current problem in less than five years old Peruvian children - Tazza, Rosana (2006)
Objective: To determine the nutritional state in less than five years Peruvian children. Design: Evaluation of antropometric indicators. Setting: Post Graduate Program in Public Nutrition, La Molina Agriculture National University and Department of Statistics and Informatics. Material and Methods: Data bases of the 1991/1992, 1996 and 2000 Demographic Surveys and Familiar Health were analyzed (Endes). Main outcome measures: Nutrition in less than five year-old children. Results: Chronic undernourishment diminished from 39% to 32%, global undernourishment from 12% to 9% and acute undernourishment from 2% to 1% during the studied period. Overweight and obese children increased from 17% and 5% to 19% and 7%, respectively. According to Endes 2000, less than five years overweight and obese children national average was 25,19%, most affected in Tacna (57%), Moquegua (42%) and Lima (41%), 48 to 59 months children, extremely poor and the urban area. According to the departmental projections, Tumbes and Ucayali would exceed 50% of overweight in 2004. The most influential variables for the outbreak of the overweight children were poverty level, child age and area of residence, discarding the social status, education level of the mother and department provenience. Conclusions: Although the undernourishment problem persists in Peruvian children, the overweight and obese are reaching considerably high values with fast increase projections.